Representasi 3D Jaringan Epidermis dan Stomata Daun Beberapa Jenis Tumbuhan Suku Apocynaceae serta Sumbangannya pada Pembelajaran Biologi SMA - Subkhi Pangestu Mukti; Ermayanti Ermayanti; Rahmi Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to produce a 3D image representation of leaf epidermis tissue in several Apocynaceae plants as enrichment material for high school biology material. The method used is a descriptive method by observing the leaf epidermis tissue in several Apocynaceae plants, namely: Adenium obesum, Catharanthus roseus, Cerbera manghas, Nerium oleander, Plumeria alba and Wrightia antidysenterica. The representation of 3D images is done using Paint-3D software and arranged in the form of a booklet. The results showed that the representation of the structure of the epidermis and stomata in the form of 3D images displayed varying characteristics. The results of the feasibility test show that the booklet has an average score of 93 and is included in the very valid category. In conclusion, the 3D image representation of the epidermal tissue with Paint-3D software can display the characteristics of the tissue structure more clearly and the booklets that are arranged are suitable for use as teaching materials. Keywords: Apocynaceae, Epidermis, 3D Representation, Stomata